NILAI UREUM, KREATININ, DAN PENYINGKIRAN KREATININ DI PENDERITA PENYAKIT GINJAL MENAHUN (KRONIK) - I. Ismail; Mutmainnah .; Hardjoeno . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Chronically Kidney Disease (CKD) is still a health problem with a high incidence, complex aetiology, and often without complaintsor clinical symptoms except in the terminal stadium. To know the distribution of CKD according to age, sex group, aetiology, determiningstage of CKD based on creatinine clearance value, a retrospective study was conducted on 88 patients of CKD at Wahidin SudirohusodoPublic Hospital of Makassar from January to December 2004. The diagnosis of CKD was based on serum ureum value (ModifiedBarthelot), serum creatinine value (Jaffe) and creatinine clearance value (Cockroft Gault). Chronically Kidney Disease was found morefrequent in men 59.09% (52 of 88). The peak age prevalence was between 50 to less than < 60 years 29.55%. The eldest patient was 83years while the youngest was 16 years. The most fragment aetiology of CKD was hypertension 18.18% (16 of 88). Based on creatinineclearance values the medium group, severe group, and renal failure group were the age group respectively 3.41%, 19.32% and 77.27%.The prevalence of CKD is found more frequent in 50 less than 60 years of age. Hypertension seems to be the more predominant aetiology,and staging based on creatinine clearance value showed that most patients were in the renal failure group.